Design and Manufacturing of Bodypack Portable Milk Machine with Capacity 5 Liters - Roni Suhartono; Adhan Efendi (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2020)
The conventional milking process by cattle breeders in hilly areas is considered ineffective and requires a lot of energy due to steep terrain and far from road access. This research aims to make a portable body type milking machine that can help farmers in the milking process. The data obtained were processed in a qualitative descriptive manner. The results showed that: (1) the stages of the study began with data collection, machine design, machine manufacturing, and performance testing; (2) performance test results show that the machine is very helpful for cattle farmers in the milk milking process.